Are consumers at the base of the pyramid willing to pay for nutritious foods? - Chege, Christine G. Kiria; Sibiko, Kenneth W.; Wanyama, Rosina; Jager, Matthias; Birachi, Eliud Abucheli (Elsevier, 2019)
Base of the Pyramid (BoP) consumers living in the urban informal settlements of developing countries spend over 60% of their income on food, yet malnutrition and micronutrient deficiency remain widespread among these populations, pointing to the inadequacy of the foods they consume in terms of quality and quantity. In this paper we examine BoP consumers’ willingness to pay (WTP) for nutritious multi-composite porridge flour (improved flour) in the informal settlements of East Africa. The analysis is based on experimental data collected from 600 households in the informal settlements of Kampala, Uganda and Nairobi, Kenya (300 in each country) in 2016. We use Tobit regression models to analyse determinants of WTP for the improved porridge flour. Results show that both Kenyan and Ugandan BoP consumers are willing to pay a premium for the improved porridge flour. In addition, providing nutrition information about the flour, characteristics of household head, economic status of the household, and presence of young children between six and 59 months in the household, influence WTP for the safe and nutritious porridge flour. The paper concludes by providing recommendations for enhancing nutrition among poor consumers in the informal settlements of developing countries.